TRANSLANGUAGING PEDAGOGY IN MULTILINGUAL ELT CLASSROOMS: STUDENT IDENTITY, STRATEGY USE, AND ACHIEVEMENT - Sahid Sahid; Nafissa Tracy; Buntara Adi Purwanto (Indonesian Journal of Education (INJOE), 2025)
This study explores the implementation of translanguaging pedagogy in multilingual English Language Teaching (ELT) classrooms, focusing on its influence on student identity construction, strategic language use, and academic achievement. Through a literature-based approach, this research synthesizes findings from previous empirical and theoretical studies to analyze how translanguaging functions as an instructional paradigm that validates learners’ linguistic repertoires and promotes more equitable learning environments. The review reveals that translanguaging supports positive identity affirmation by enabling students to draw on their full linguistic resources, thus fostering a sense of belonging and reducing linguistic anxiety. In terms of strategy use, existing studies demonstrate that translanguaging enhances metalinguistic awareness, deepens comprehension, and facilitates flexible language negotiation practices that strengthen communicative competence. The literature also shows that the integration of translanguaging practices contributes to improved academic achievement, particularly through scaffolding complex tasks and enhancing engagement in multilingual settings. Overall, the synthesis highlights that translanguaging pedagogy serves as a transformative framework for multilingual ELT classrooms by bridging linguistic diversity with instructional effectiveness, thereby supporting learners’ holistic linguistic and academic development.